COMPARATIVE CHARACTERISTIC OF CALCIUM AND MAGNESIUM CONTENT IN THE JUICES OF SOME LIGNEOUS PLANTS OF VINNITSA REGION DEPENDING ON THE GROWTH CONDITIONS - Bobrovskaya, O.A.; Novitskaya, M.V. (World of Medicine and Biology, 2016)
The results of research of juice obtained from some ligneous plants of Vinnitsa region, namely from Birch (Betula verrucosa), Maple (Acer ginnala) and Hornbeam (Carpinus betulus) are presented in this article. The basic morphological and physiological characteristics of specified above trees are considered. The methods of collection and storage of juices are worked out. The comparative analysis of some organoleptic properties of juice of selected ligneous plants is carried out. Experimentally, quantitative content of calcium and magnesium in the juices of ligneous plants is defined by chelatometry and comparative analysis of presence of these minerals depending on environmental conditions tree growth is carried out. It was found that the highest number of calcium and magnesium contained in the birch juice, the lowest number is in the hornbeam juice, although Hornbeam (Carpinus betulus) belongs to the family Birch (Betulaseae). The increase of calcium and magnesium in the trees juice depending on the growth location are observed. The Researched juice can be used as vitamin drink and as a natural source of calcium and magnesium during the spring beriberi.
Keywords: juice; ligneous plants; growing conditions; calcium; magnesium; quantitative content; chelatometry